Integrating clinical care and medical education during the 2026 Arbaeen mass gathering - Sakina Rizvi; Syed M. Qasim Jaffry (Journal of the Pakistan Medical Association, 2026)
The Arbaeen pilgrimage in Karbala, Iraq, creates substantial temporary healthcare demand while providing opportunities for education in mass-gathering medicine. During the 18th Annual Arbaeen Medical Mission, Imamia Medics International operated a multidisciplinary Medical Camp and Teaching Field Hospital from July 28 to August 4, 2026. During this period, 32,064 patient encounters were recorded, comprising 27,189 medical, emergency and specialtycare encounters, 2,525 eye-care encounters and 2,350 dental encounters. Clinical service was integrated with structured medical education. Forty-four medical students from two Iraqi universities participated in scheduled clinical rotations with supervised clinical exposure and structured assessment. Fourteen educational programmes were delivered through 15 teaching sessions, generating 172 participantattendances and covering clinical medicine, procedural skills, emergency response, trauma, mass-casualty management and artificial intelligence. This experience demonstrates the feasibility of integrating high-volume mass-gathering healthcare with structured clinical education and workforce development through a Teaching Field Hospital model.